Porous film, air-permeable member, and member supply sheet
Patent Information
- Application Number
- CN202580024800.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-24
- Publication Date
- 2026-11-03
AI Technical Summary
Fluorine-free porous membranes, while providing practical breathability, are prone to breakage when peeled off from the release liner, resulting in limited maneuverability and making it difficult to balance breathability and maneuverability.
The porous membrane, made primarily of fluorine-free thermoplastic resin, has an air permeability of less than 200 seconds/100mL and a cohesion of more than 1.0N/20mm. It is fixed to the object through an adhesive layer to prevent damage.
It achieves improved controllability of porous membranes without compromising air permeability, ensures no agglomeration or damage occurs during peeling, and is suitable for various applications.
Smart Images

Figure CN123036333A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to porous membranes, breathable components, and sheet for supplying components. Background Technology
[0002] Fluorinated resin porous membranes are used in various applications such as filters, sound-permeable membranes, air-permeable membranes, and diaphragms. Fluorine-free porous membranes have also been proposed for these applications.
[0003] For example, Patent Document 1 discloses an olefin resin microporous biaxial stretching membrane, which is an olefin resin microporous biaxial stretching membrane with micropores and containing olefin resin, and has a puncture strength of 0.7N or more and an air permeability of 75s / 100mL to 400s / 100mL.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-095576 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] Porous membranes used to ensure air permeability through openings in the housing or similar parts of a device while preventing foreign objects from passing through are sometimes provided as components laminated with a release liner. Such porous membranes are used by peeling them off from the release liner when placed on the open surface of the housing or similar part. However, according to the inventors' research, while fluorine-free porous membranes provide practical air permeability, they sometimes break when peeled off from the release liner. The breakage of fluorine-free porous membranes can also become a problem after being placed on an open surface. The possibility of breakage of fluorine-free porous membranes with practical air permeability limits maneuverability, and there is room for improvement in this regard.
[0009] Therefore, the object of the present invention is to provide a porous membrane, a breathable component, and a component supply sheet that are suitable for balancing maneuverability and breathability.
[0010] means for solving problems
[0011] The present invention provides a porous membrane, wherein the porous membrane comprises a fluorine-free thermoplastic resin as the main component, the air permeability of the porous membrane is less than 200 seconds / 100mL as expressed in Gurley number, and the cohesion of the porous membrane is greater than 1.0N / 20mm.
[0012] In another aspect, the present invention provides a breathable member having: the porous membrane of the present invention described above and an adhesive layer bonded to the porous membrane.
[0013] This invention provides a breathable member disposed on the surface of an object having an opening, wherein... The breathable component has: A porous membrane having a shape that covers the opening; and A first adhesive layer is bonded to the first main surface of the porous membrane. The breathable component is fixed to the surface of the object using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operability evaluation test was performed, the porous membrane did not undergo aggregation or damage until at least 0.03 N / 2.0 mm. <Manipulation Evaluation Test> Double-sided adhesive tape is bonded to the second main side of the porous membrane, and a release liner is bonded to the double-sided adhesive tape. Next, a roller is moved back and forth once on the release liner while a load of 2 kg is applied. Then, the breathable component is cured at 60°C for 5 minutes. The cured breathable component is then placed at room temperature for 15 minutes, and then the release liner is grasped with tweezers and lifted to peel it off.
[0014] In another aspect, the present invention provides a component supply sheet having: A breathable member disposed on the surface of an object having an opening; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; and An adhesive layer is bonded to the porous membrane. The porous membrane is the porous membrane of the present invention described above.
[0015] In another aspect, the present invention provides a component supply sheet having: A breathable member disposed on the surface of an object having an opening; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; A first adhesive layer is bonded to a first main surface of the porous membrane; A second adhesive layer is bonded to the second main surface of the porous membrane; and The release liner is then bonded to the second adhesive layer. The second adhesive layer is disposed between the release liner and the porous membrane. The breathable component is fixed to the surface of the substrate sheet using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operational evaluation tests were performed, the porous membrane did not undergo aggregation or damage. <Manipulation Evaluation Test> The first adhesive layer is peeled off from the substrate sheet, bringing it into contact with a stainless steel test plate, thereby placing the breathable component on the test plate. Next, a roller is moved back and forth once on the release liner while a 2 kg load is applied, thereby securing the breathable component to the test plate. Then, the breathable component is cured at 60°C for 5 minutes. After curing, the breathable component is left at room temperature for 15 minutes, and then the release liner is grasped with tweezers and lifted to peel off.
[0016] Invention Effects
[0017] According to the present invention, it is possible to provide porous membranes, breathable components, and component supply sheets that are suitable for balancing maneuverability and breathability. Attached Figure Description
[0018] Figure 1 A cross-sectional view illustrating an example of the porous membrane of the present invention.
[0019] Figure 2 To indicate the use of measurement Figure 1 A schematic diagram of the T-type peel test method for the cohesiveness of porous membranes.
[0020] Figure 3 A cross-sectional view illustrating an example of the membrane component of the present invention.
[0021] Figure 4 To illustrate Figure 3 A cross-sectional view of a deformed membrane component, Example 1.
[0022] Figure 5 To illustrate Figure 3A cross-sectional view of a modified example 2 (wound body) of a membrane component.
[0023] Figure 6 A cross-sectional view illustrating an example of the breathable component of the present invention.
[0024] Figure 7 To illustrate Figure 6 A cross-sectional view of a modified example 1 of a breathable component.
[0025] Figure 8 To illustrate Figure 6 A cross-sectional view of a modified example 2 of the ventilated component.
[0026] Figure 9 To illustrate Figure 6 A cross-sectional view of a modified example 3 of the ventilated component.
[0027] Figure 10 To illustrate Figure 6 A cross-sectional view of a modified example 4 of the ventilated component.
[0028] Figure 11 To illustrate Figure 6 A cross-sectional view of a modified example 5 of a breathable component.
[0029] Figure 12 A cross-sectional view illustrating another example of the breathable component of the present invention.
[0030] Figure 13 For illustrative purposes Figure 12 A schematic cross-sectional view of the controllability evaluation test of the breathable component.
[0031] Figure 14 To illustrate Figure 12 A cross-sectional view of a modified example of a breathable component.
[0032] Figure 15 A cross-sectional view illustrating an example of the component supply sheet of the present invention.
[0033] Figure 16 To illustrate Figure 15 A cross-sectional view of a modified example 1 of the component supply sheet.
[0034] Figure 17 For illustrative purposes Figure 16 A schematic cross-sectional view of the controllability evaluation test of the component supply sheet.
[0035] Figure 18 To illustrate Figure 15 A cross-sectional view of a modified example 2 of the component supply sheet.
[0036] Figure 19AA figure (2500x magnification) showing the results of observing the surface of the porous membrane of Example 5 using a scanning electron microscope (SEM).
[0037] Figure 19B for Figure 19A A magnified view of a portion (10,000x).
[0038] Figure 19C A graph (1500x magnification) showing the results of SEM observation of the cross-section of the porous membrane of Example 5.
[0039] Figure 20A A figure (2500x magnification) showing the results of SEM observation of the surface of the porous membrane in Comparative Example 2.
[0040] Figure 20B for Figure 20A A magnified view of a portion (10,000x).
[0041] Figure 20C A figure (1500x magnification) showing the results of SEM observation of the cross-section of the porous membrane of Comparative Example 2. Detailed Implementation
[0042] The porous membrane of the first embodiment of the present invention comprises a fluorine-free thermoplastic resin as the main component, the air permeability of the porous membrane is less than 200 seconds / 100 mL in terms of Grylloy number, and the cohesion of the porous membrane is more than 1.0 N / 20 mm.
[0043] In a second aspect of the invention, for example, in the porous membrane of the first aspect, the thermoplastic resin is a polyolefin resin.
[0044] In a third aspect of the present invention, for example, the thickness of the porous membrane in the first or second aspect is 40 μm or more and 100 μm or less.
[0045] In the fourth aspect of the present invention, for example, the porous membrane of any one of the first to third aspects has a water pressure resistance of 200 kPa or more.
[0046] In the fifth aspect of the present invention, for example, the porous membrane of any one of the first to fourth aspects is a stretched membrane.
[0047] The breathable member of the sixth aspect of the present invention, for example, has: a porous membrane of any one of the first to fifth aspects; and an adhesive layer bonded to the porous membrane.
[0048] In a seventh aspect of the invention, for example, in the breathable member of the sixth aspect, the adhesive layer comprises: a first adhesive layer bonded to a first main surface of the porous membrane, and a second adhesive layer bonded to a second main surface of the porous membrane.
[0049] In an eighth aspect of the invention, for example, the breathable member of the seventh aspect further includes a release liner, with a second adhesive layer disposed between the release liner and the porous membrane, the second adhesive layer being bonded to the release liner.
[0050] A breathable member according to a ninth aspect of the present invention is disposed on the surface of an object having an open surface, wherein the breathable member has: A porous membrane having a shape that covers the opening; and A first adhesive layer is bonded to the first main surface of the porous membrane. The breathable component is fixed to the surface of the object using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operational evaluation test was performed, the porous membrane did not undergo agglomeration failure until at least 0.03 N / 2.0 mm.
[0051] <Manipulation Evaluation Test>
[0052] Double-sided adhesive tape is bonded to the second main side of the porous membrane, and a release liner is bonded to the double-sided adhesive tape. Next, a roller is moved back and forth once on the release liner while a load of 2 kg is applied. Then, the breathable component is cured at 60°C for 5 minutes. The cured breathable component is then placed at room temperature for 15 minutes, and then the release liner is grasped with tweezers and lifted to peel it off.
[0053] In a tenth aspect of the invention, for example, the breathable member of the ninth aspect has a second adhesive layer that is bonded to the second main surface of the porous membrane.
[0054] The eleventh embodiment of the present invention provides a component supply sheet comprising: a breathable member disposed on the surface of an object having an open surface; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; and an adhesive layer bonded to the porous membrane. The porous membrane is, for example, a porous membrane of any of the first to fifth methods.
[0055] In the twelfth aspect of the present invention, for example, in the component supply sheet of the eleventh aspect, a plurality of the breathable components are disposed on the surface of the substrate sheet.
[0056] The component supply sheet of the thirteenth embodiment of the present invention comprises: a breathable member disposed on the surface of an object having an open surface; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; A first adhesive layer is bonded to a first main surface of the porous membrane; A second adhesive layer is bonded to the second main surface of the porous membrane; and The release liner is then bonded to the second adhesive layer. The second adhesive layer is disposed between the release liner and the porous membrane. The breathable component is fixed to the surface of the substrate sheet using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operational evaluation tests were performed, the porous membrane did not undergo aggregation or damage. <Manipulation Evaluation Test> Peel the first adhesive layer from the substrate sheet, bringing the first adhesive layer into contact with a stainless steel test plate, thereby placing the breathable member on the test plate. Then, while applying a 2 kg load, roll a roller back and forth once on the release liner, thereby fixing the breathable member to the test plate. Next, cure the breathable member at 60°C for 5 minutes. After curing, place the breathable member at room temperature for 15 minutes, then use tweezers to grasp the release liner and lift it to peel it off.
[0057] In the fourteenth aspect of the present invention, for example, in the component supply sheet of the thirteenth aspect, a plurality of the breathable components are disposed on the surface of the substrate sheet.
[0058] The method for manufacturing a porous membrane according to the fifteenth aspect of the present invention includes: The process of mixing a composition containing a fluorine-free thermoplastic resin and a plasticizer to obtain a compound; The process of performing compression or extrusion processing; The process of implementing cooling treatment; The process of performing stretching treatment; and The process of extracting and treating plasticizers is implemented. Following the stretching process, a pressing process is also included.
[0059] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the following embodiments.
[0060] [Porous membrane]
[0061] An example of the porous membrane of the present invention is shown in Figure 1 middle. Figure 1 The porous membrane 1 contains a fluorine-free thermoplastic resin as its main component. "Main component" refers to the component with the highest content by weight in the porous membrane 1. With this configuration, the porous membrane 1 can, for example, be bonded to an object such as a device housing using a hot-melt adhesive without the need for an adhesive layer.
[0062] The thickness-direction air permeability of the porous membrane 1, expressed as a Graeme number, is less than 200 seconds / 100 mL. Therefore, the porous membrane 1 exhibits high air permeability. In this specification, "Graeme number" refers to the air permeability resistance (Graeme permeability) measured according to the Wang Yan test machine method specified in JIS P8117:2009.
[0063] The upper limit of the air permeability of the porous membrane 1 can be expressed in terms of Graeme number as below 190 seconds / 100 mL, below 180 seconds / 100 mL, below 170 seconds / 100 mL, below 160 seconds / 100 mL, and further below 150 seconds / 100 mL. The lower limit of the air permeability of the porous membrane 1 can be expressed in terms of Graeme number as above 0.1 seconds / 100 mL, above 1 second / 100 mL, above 10 seconds / 100 mL, and further above 15 seconds / 100 mL. The permeability of the porous membrane 1 can be greater than 0.1 seconds / 100 mL and less than 190 seconds / 100 mL, greater than 0.1 seconds / 100 mL and less than 180 seconds / 100 mL, greater than 0.1 seconds / 100 mL and less than 170 seconds / 100 mL, greater than 0.1 seconds / 100 mL and less than 160 seconds / 100 mL, and further greater than 0.1 seconds / 100 mL and less than 150 seconds / 100 mL.
[0064] It should be noted that even if the size of the porous membrane 1 does not meet the recommended size (50mm×50mm) of the test piece for the Wang Yan test machine method, the air permeability resistance (Gerley air permeability) can still be evaluated based on the Wang Yan test machine method by using a measuring fixture.
[0065] The measuring fixture has a shape and size suitable for mounting on the air permeability measuring section of a pressure testing machine, and is designed with a thickness and material that will not deform due to the pressure difference applied to the test piece during air permeability resistance measurement. An example of the measuring fixture is a SUS circular plate with a thickness of 2 mm and a diameter of 47 mm. A through-hole with an opening smaller than the size of the membrane being evaluated is pre-formed at the center of the surface of the measuring fixture. The cross-section of the through-hole is typically circular, and its diameter is set such that the opening of the through-hole is completely covered by the membrane being evaluated. For example, a diameter of 1 mm or 2 mm can be used for the through-hole. Next, the porous membrane 1 being evaluated is fixed to one surface of the measuring fixture in a manner that covers the opening. The fixing is performed in such a way that, during the air permeability resistance measurement, air only passes through the effective test section of the porous membrane 1 (the portion overlapping the opening when viewed from a direction perpendicular to the main surface of the fixed porous membrane 1), and the fixed portion does not obstruct the passage of air in the effective test section of the porous membrane 1. The porous membrane 1 can be fixed using double-sided adhesive tape with a vent cut out at the center, the shape of which matches the opening. The double-sided adhesive tape is positioned between the measuring fixture and the porous membrane 1, with the vent surrounding it aligned with the opening. Next, the measuring fixture with the porous membrane 1 fixed is placed in the air permeability measuring section of the Wang Yan type testing machine, with the fixed surface of the porous membrane 1 facing downstream of the airflow during measurement. The test is performed using the Wang Yan type testing machine method, and the air permeability resistance indication value t shown on the testing machine is recorded. Then, the formula t can be used... K ={t×(area of the effective test section of porous membrane 1 [cm²])} 2 ]) / 6.452[cm 2 The recorded air permeability resistance indicator value t is converted into the 6.452 cm value specified in the Wang Yan-style testing machine method. 2 The effective test area value t K and the obtained conversion value t K The air permeability resistance (Gerley air permeability) of the porous membrane 1 was measured according to the Wang Yan-style testing machine method. It should be noted that it was confirmed that the air permeability resistance measured without the use of a measuring fixture for the porous membrane 1 with the recommended test piece size (50mm×50mm) that meets the Wang Yan-style testing machine method is highly consistent with the air permeability resistance measured with the measuring fixture after the porous membrane 1 is made into a small piece. That is, the use of the measuring fixture has no substantial effect on the measured value of the air permeability resistance.
[0066] The cohesion of the porous membrane 1 is 1.0 N / 20 mm or more. With this configuration, cohesion failure when the porous membrane 1 is installed on the housing of the device is suppressed, and it has appropriate controllability.
[0067] The upper limit of the cohesion of the porous membrane 1 can be below 4.0 N / 20 mm, below 3.5 N / 20 mm, or below 3.0 N / 20 mm.
[0068] The cohesion of the porous membrane 1 can be implemented according to JIS Z0237:2009 by the method described below.
[0069] Figure 2 This is a schematic diagram illustrating the method for a T-type peel test used to determine the cohesiveness of a porous membrane 1. First, the porous membrane 1 is cut to a size of 100 mm in length and 20 mm in width. Next, two double-sided adhesive tapes 51 (manufactured by Nitto Denko Corporation, No. 5610) with the same shape as the cut porous membrane 1 are prepared. Each double-sided adhesive tape 51 is adhered to one and the other side of the porous membrane 1, respectively, with its outer periphery aligned with both sides. Next, two PET films 52 (25 μm thick), each 150 mm in length and 20 mm in width, are prepared. Each PET film 52 is adhered to one and the other side of the porous membrane 1, respectively, using the double-sided adhesive tapes 51. The PET films 52 are adhered in such a manner that the two ends of each PET film 52 in the width direction are aligned with the two ends of the porous membrane 1 in the width direction, and when viewed from a direction perpendicular to the main surface of the PET film 52, the two ends of each PET film 52 in the length direction do not overlap with the porous membrane 1 and the double-sided adhesive tapes 51. However, the length (in the length direction) of the free end of each PET film 52 is such that the chuck of the tensile testing machine can stably grip the length of the PET film 52 (e.g., 25 mm). Next, a pressing force is applied in the thickness direction of the laminate 50 of PET film 52 / double-sided adhesive tape 51 / porous film 1 / double-sided adhesive tape 51 / PET film 52, and the rollers are moved back and forth once while a load of 2 kg is applied. Then, the laminate is cured at 60°C for 2 hours. The laminate, cooled to room temperature for 30 minutes, is used as the test piece 50.
[0070] Next, a tensile testing machine (e.g., the Autograph AGS-X benchtop precision universal testing machine manufactured by Shimadzu Corporation) is prepared. The free end of one PET film 52 at one end of the test piece 50 along its length is fixed to the upper chuck 61 of the tensile testing machine. The free end of another PET film 52 at the other end of the test piece 50 along its length is mounted to the lower chuck 62. Then, under the conditions of a test temperature of 25°C and a tensile speed of 100 mm / min, a tensile test is performed by stretching the upper end of one PET film 52 upwards, thereby causing the porous membrane 1 to coagulate and break. After the start of the test, the stress measured between the chucks at the initial 25 mm displacement is ignored, and the average value of the measured stress (N) continuously recorded at the subsequent 50 mm displacement is taken as the cohesive force (N / 20 mm) of the porous membrane 1.
[0071] As described above, the porous membrane 1 contains a fluorine-free thermoplastic resin as its main component. The fluorine-free thermoplastic resin can be a polyolefin resin. By using a polyolefin resin as the thermoplastic resin, it is easy to obtain a porous membrane 1 that balances controllability and air permeability.
[0072] Polyolefin resins include polyethylene (PE) resin, polypropylene (PP) resin, and polymethylpentene (PMP) resin.
[0073] Polyolefin resins can be polymethylpentene resins. Polymethylpentene resins refer to homopolymers or copolymers of poly(4-methyl-1-pentene) resins, poly(3-methyl-1-pentene) resins, etc. As copolymers, there are random copolymers and block copolymers, etc. From the viewpoint of heat resistance and processability, homopolymers of poly(4-methyl-1-pentene) resins are preferred.
[0074] Polyolefin resins can be poly(4-methyl-1-pentene) resins. Poly(4-methyl-1-pentene) resins refer to homopolymers of 4-methyl-1-pentene, or copolymers of 4-methyl-1-pentene with at least one α-olefin. The ratio of 4-methyl-1-pentene to α-olefin in the copolymer can be adjusted within a range above 180°C.
[0075] The fluorine-free thermoplastic resin can be a thermoplastic resin with a melting point above 180°C and below 300°C. When the melting point of the thermoplastic resin is above 180°C, sufficient heat resistance can be ensured in the porous membrane 1. When the melting point of the thermoplastic resin is below 300°C, the porous membrane 1 can be formed, for example, by melt molding.
[0076] The melting point of thermoplastic resins can be above 200°C and below 280°C, and more specifically, above 220°C and below 260°C.
[0077] The water pressure resistance of the porous membrane 1 is evaluated according to the water resistance test method B (high water pressure method) specified in JIS L1092:2009, and preferably above 200 kPa.
[0078] The lower limit of the water pressure resistance of the porous membrane 1 can be above 220 kPa, above 240 kPa, or above 250 kPa. The upper limit of the water pressure resistance of the porous membrane 1 is, for example, below 2000 kPa. The water pressure resistance of the porous membrane 1 can be above 220 kPa and below 2000 kPa, above 240 kPa and below 2000 kPa, or above 250 kPa and below 2000 kPa.
[0079] The water pressure resistance of the porous membrane 1 can be measured using a testing fixture, according to the water resistance test method described above, as follows. One example of the testing fixture is a 47mm diameter stainless steel (SUS) circular plate with a centrally located through-hole (having a circular cross-section) and a diameter of 1.0mm. This circular plate has a thickness that will not deform under the water pressure applied during the water pressure resistance test. The water pressure resistance test using this fixture can be performed as follows.
[0080] The porous membrane 1, which is the object of evaluation, is fixed to one side of the measuring fixture by covering the opening of the through hole. The fixing is performed in a manner that prevents water leakage from the fixed portion of the membrane during the water pressure resistance test. For fixing the porous membrane 1, a double-sided adhesive tape with a perforation (1.6 mm in diameter) punched out at the center, matching the shape of the opening, can be used. The double-sided adhesive tape is positioned between the measuring fixture and the porous membrane 1, with the perforation surrounding it aligned with the opening. Next, the measuring fixture with the porous membrane 1 fixed is placed in the test apparatus such that the side of the porous membrane 1 opposite to the fixed surface becomes the water pressure application surface during the test. The water pressure resistance is measured according to Water Resistance Test Method B (High Water Pressure Method) as specified in JIS L1092:2009. The water pressure resistance is measured based on the water pressure when water flows out from a point on the membrane surface of the porous membrane 1. The measured water pressure resistance can be taken as the water pressure resistance of the porous membrane 1. The test apparatus can be a device with the same configuration as the water resistance test apparatus illustrated in JIS L1092:2009, and with a test piece mounting structure capable of setting the aforementioned measuring fixture.
[0081] The porous membrane 1 can be in the form of a membrane or a sheet. The thickness of the porous membrane 1 is preferably 40 μm or more and 100 μm or less. When the thickness is within the above-mentioned range, the controllability of the porous membrane 1 can be improved.
[0082] The thickness of the porous membrane 1 can be determined, for example, by measuring the thickness at any 5 points on the porous membrane 1 using a dial indicator and averaging these measurements. Alternatively, the thickness of the porous membrane 1 can be measured at any 5 points in a cross-sectional SEM image of the porous membrane 1 and averaged as the result.
[0083] The lower limit of the thickness of porous membrane 1 can be above 44 μm. The upper limit of the thickness of porous membrane 1 can be below 90 μm, below 80 μm, or below 70 μm.
[0084] The porous membrane 1 can have a tortoise-shell-like structure formed by multiple nodes and multiple fibrils. This tortoise-shell-like structure can exist throughout the porous membrane 1. A porous membrane 1 with such a structure is suitable for balancing maneuverability and air permeability. The tortoise-shell-like structure can be identified, for example, by observing the main surface of the porous membrane 1 from a vertical direction. In this disclosure, "main surface" refers to the surface with the largest area of the membrane or sheet-like component. It should be noted that in this disclosure, the terms "main surface," "surface," and "surface" are used interchangeably with "main surface" for the porous membrane 1.
[0085] In this disclosure, "a tortoise-shell-like structure formed by multiple nodes and multiple fibrils" refers to a structure that can be confirmed by observing the surface of the porous membrane 1 using a scanning electron microscope (SEM). It refers to a structure in which island-like regions formed by multiple nodes are irregularly connected, and these island-like regions are interconnected by multiple fibrils. The island-like regions may, for example, have a polygonal shape. It should be noted that the shape of the polygonal region does not necessarily have to be composed only of straight lines; it also includes approximately polygonal regions with some sides being curved, such as arcs. Furthermore, the polygonal shape is not limited to a hexagonal shape.
[0086] For example, Figure 19A A figure (2500x magnification) showing the results of SEM observation of the surface of the porous membrane of Example 5 described later. Figure 19B for Figure 19A A magnified view of a portion (10000x). For example... Figure 19A and Figure 19B As shown, the surface of the porous membrane in Example 5 has a tortoise-shell-like structure formed by multiple nodes and multiple fibrils.
[0087] When observing the cross-section of the porous membrane 1 using SEM, multiple nodes can be observed along the thickness direction. These multiple nodes can exist throughout the entire thickness direction of the porous membrane 1. They can also exist uniformly along the thickness direction of the porous membrane 1. Adjacent block nodes can be connected to each other via multiple fibrils, or they can be directly connected without multiple fibrils.
[0088] Preferably, the porous membrane 1 has island-like regions formed by multiple nodes in the thickness direction with small deviations in the size of the gaps between them and the gaps being dispersed. Porous membrane 1 with such a cross-sectional structure exhibits a tendency to improve cohesion while maintaining high air permeability. The gaps present in the thickness direction contribute to the improvement of air permeability of the porous membrane 1. On the other hand, when there are deviations in the size of the gaps in the thickness direction, for example, when large gaps are mixed with small gaps, the cohesion of the porous membrane 1 tends to decrease. However, when the deviations in the size of the gaps in the thickness direction are small and the gaps are dispersed, the cohesion of the porous membrane 1 is improved, thus achieving a balance between high air permeability and high cohesion.
[0089] For example, Figure 19C A graph (1500x magnification) showing the results of SEM observation of the cross-section of the porous membrane of Example 5 described later. Figure 19C As shown, when the cross-section of the porous membrane of Example 5 is observed using SEM, it contains multiple nodes along the thickness direction. These multiple nodes exist throughout the entire thickness direction of the porous membrane. In the porous membrane of Example 5, the island-like regions formed by the multiple nodes along the thickness direction exhibit small deviations in the size of their gaps, and the gaps are dispersed.
[0090] The porosity of the porous membrane 1 is, for example, 25% or more. The porosity of the porous membrane 1 can be 20% or more, or 35% or more. The porosity can be calculated by substituting the weight, thickness, area (area of the main surface) and true density of the porous membrane 1 into the following formula (1).
[0091] Porosity (%) = {1 - (weight [g] / (thickness [cm] × area [cm])} 2 ]×True density [g / cm³] 3 ]))}×100···Equation (1)
[0092] The upper limit of the porosity of the porous membrane 1 is, for example, 95%. The upper limit of the porosity can be 90%.
[0093] The porous membrane 1 can be a stretched membrane. When the porous membrane 1 is a stretched membrane, it is easy to control air permeability and cohesion. The stretched membrane can be a biaxial stretched membrane or a uniaxial stretched membrane.
[0094] At least one main surface of the porous membrane 1 can be subjected to a surface modification treatment. Examples of surface modification treatments include: oil-repellent treatment, chemical treatment, sputtering etching treatment, plasma treatment, etc. In the area where the surface modification treatment has been performed, the adhesion of the porous membrane 1 is improved.
[0095] Liquid-repellent treatment can be applied to at least one main surface of the porous membrane 1. The liquid-repellent treatment is typically performed by coating the surface of the porous membrane 1 with a liquid-repellent agent or by immersing the porous membrane 1 in a liquid-repellent agent. There are no particular limitations on the liquid-repellent agent; it can be a fluorinated liquid-repellent agent, an organosilicon liquid-repellent agent, or an acrylic liquid-repellent agent. Fluorinated liquid-repellent agents, for example, have a structure with a fluorine-saturated hydrocarbon side chain (perfluoroalkyl) on the main chain of an acrylic resin.
[0096] [Methods for manufacturing porous membranes]
[0097] The porous membrane 1 described above can be manufactured, for example, by the following method.
[0098] The method for manufacturing the porous membrane 1 includes, for example,: mixing a composition comprising a fluorine-free thermoplastic resin and a plasticizer to obtain a compound (step S1); pressing the compound to obtain a first pressed body (step S2); cooling the first pressed body to obtain a molded body (step S3); stretching the molded body to obtain a sheet (step S4); pressing the sheet a second time to obtain a second pressed body (step S5); and extracting the plasticizer from the second pressed body (step S6).
[0099] Alternatively, as another method, the manufacturing method of the porous membrane 1 includes, for example,: mixing a composition comprising a fluorine-free thermoplastic resin and a plasticizer to obtain a compound (step ST); extruding the compound using a twin-screw extruder (step ST2); cooling the extruded compound to obtain a molded body (step ST3); stretching the molded body to obtain a sheet (step S4); pressing the sheet to obtain a pressed body (step S5); and extracting the plasticizer from the pressed body (step S6).
[0100] Steps S1 to S3 correspond to the process of preparing the precursor for the porous membrane 1. Steps S4 to S6 correspond to the process of growing the porous structure.
[0101] Step S1 is performed, for example, at a temperature of 230°C to 260°C for 5 to 30 minutes.
[0102] As a fluorine-free thermoplastic resin, polymethylpentene resin can be used, for example.
[0103] In the composition comprising a thermoplastic resin and a plasticizer, resins such as polyethylene, polypropylene, poly-1-butene, and cyclic polyolefins may be mixed within a range that does not affect the properties of the porous membrane 1.
[0104] Plasticizers are non-volatile solvents that, when mixed with thermoplastic resins such as polymethylpentene, form a mixture at a temperature above the resin's melting point and exhibit thermally induced phase separation upon cooling. Plasticizers can be liquid or solid at room temperature. They can be used alone or in combination with other plasticizers.
[0105] The mixing ratio of thermoplastic resin and plasticizer is set in a manner that allows for the formation of a uniform compound in step S1 and the formation of a molded article in step S3. Specifically, the weight ratio of thermoplastic resin in the composition comprising thermoplastic resin and plasticizer is, for example, 20% by weight or more and 80% by weight or less, preferably 30% by weight or more and 70% by weight or less. By using a weight ratio of thermoplastic resin of 20% by weight or more, excessive reduction in the viscosity of the composition can be avoided. By using a weight ratio of thermoplastic resin of 80% by weight or less, a good porous structure is easily obtained.
[0106] In a composition containing a thermoplastic resin and a plasticizer, additives such as antioxidants, nucleating agents, antistatic agents, flame retardants, lubricants, UV absorbers, colorants, and inorganic fillers for improving strength may be further mixed in, depending on the purpose.
[0107] Step S2 is performed, for example, at a temperature of 230°C to 260°C for 2 to 30 minutes. The thickness of the first pressed body obtained by step S2 is, for example, 0.1 mm.
[0108] In step S3, for example, the first pressed body obtained in step S2 is brought into contact with a heat conductor and cooled to a temperature sufficiently low than the crystallization temperature of the thermoplastic resin to cure it. Examples of heat conductors used for cooling include water, air, metal, and plasticizers.
[0109] The manufacturing method may also include extruding the compound using a twin-screw extruder (step ST2) instead of step S2. In step ST2, the compound can be extruded onto metal rollers with controlled surface temperature. A flat die (coat hanger die) can be used in the extrusion of the compound. By using a flat die, the compound can be extruded in a wide width, thus easily obtaining a sheet-like formed body in step ST2.
[0110] In the case where step ST2 replaces step S2, the manufacturing method may also include cooling the extruded compound to obtain a shaped body (step ST3) instead of step S3. In step ST3, for example, a metal roller with a controlled surface temperature can be used to stretch the compound while cooling it, thereby obtaining a sheet-like shaped body. The surface temperature of the metal roller is controlled, for example, at 120°C. There can be multiple metal rollers. By passing the compound through multiple metal rollers, a sheet-like shaped body can be formed while cooling is being performed.
[0111] In step S4, the molded body is stretched at least once in at least one uniaxial direction. Stretching in at least one uniaxial direction includes longitudinal uniaxial stretching, transverse uniaxial stretching, simultaneous biaxial stretching, and successive biaxial stretching. The molded body can be stretched sequentially or simultaneously. Through step S4, pores are generated in the molded body, and a tortoise-shell-like structure formed by multiple nodes and multiple fibrils is created.
[0112] The stretching temperature can be 20℃~240℃, 50℃~230℃, or 100℃~220℃ for longitudinal and transverse stretching, respectively.
[0113] The stretch ratio, measured in the longitudinal and / or transverse uniaxial direction, can be 2.0 to 10.0 times, 2.0 to 8.0 times, or 2.0 to 5.0 times.
[0114] The strain rate during tension can be 1% / second to 10% / second, 1% / second to 8% / second, or 1% / second to 5% / second in the longitudinal and / or transverse directions. When the strain rate is within the above range, a porous membrane exhibiting good air permeability can be obtained.
[0115] Step S5 is performed, for example, at a temperature of 80°C to 200°C and a pressure of 2 kPa to 10 kPa for 2 to 30 minutes. The hot-pressing temperature of step S5 is preferably below the melting point of the thermoplastic resin. The thickness of the second pressed body obtained through step S5 is, for example, 100 μm or less. Through step S5, deviations in the size of the gaps in the thickness direction of the second pressed body are suppressed, and the gaps are dispersed. This results in improved cohesion of the finally obtained porous membrane 1.
[0116] In step S6, the plasticizer is removed from the second compressed body or sheet, for example, using an extraction solvent. After step S6, the second compressed body or sheet after the plasticizer has been removed can be dried using a dryer or by natural drying. The porous membrane 1 can be obtained through the above operations.
[0117] As the extraction solvent, it is preferable to use a solvent that is a poor solvent for thermoplastic resins such as polymethylpentene resin, but a good solvent for plasticizers, and whose boiling point is lower than the melting point of porous membrane 1. Examples of such extraction solvents include: hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and 2-butanone. When safety is a consideration, alcohols and ketones are preferred. Methyl ethyl ketone (MEK) can be used as an extraction solvent.
[0118] Between steps S4 and S5, heat curing can be performed on the sheet. Heat curing can be performed, for example, using a hot air circulating oven. By performing heat curing, the thermal shrinkage of the stretched sheet can be reduced. The heat curing temperature is, for example, 50°C to 240°C. The heat curing temperature can also be 100°C to 230°C, or even 150°C to 220°C.
[0119] Heat setting can be performed after step S4, between steps S4 and S5, or both after steps S4 and S5. Examples of heat setting methods include: using a tenter frame to fix the width direction and continuously passing the product through a heat treatment furnace; applying appropriate tension and continuously passing the product through a heat treatment furnace without fixing the width direction; and winding the product into rolls and feeding them into the heat treatment furnace in batches.
[0120] [Membrane Components]
[0121] An example of the membrane component of the present invention is shown in Figure 3 middle. Figure 3 The membrane component 2 (2A) has a porous membrane 1. Figure 4 The middle shows Figure 3 Example 1: Deformation of a membrane component. Figure 4 The membrane component 2 (2B) also has a breathable support material 3. The breathable support material 3 is laminated on the porous membrane 1. The breathable support material 3 improves the strength and operability (operability) of the membrane component 2.
[0122] The breathable support material 3 typically has higher air permeability in the thickness direction compared to the porous membrane 1. Examples of the breathable support material 3 are woven fabrics, nonwoven fabrics, meshes, and openwork. Examples of materials constituting the breathable support material 3 are polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene (PE) and polypropylene (PP), and aromatic polyamide resins. When viewed from a direction perpendicular to the main surface of the membrane member 2, the shape of the breathable support material 3 may be the same as or different from that of the porous membrane 1. When viewed from a direction perpendicular to the main surface of the membrane member 2, the breathable support material 3 may have a peripheral portion corresponding to the peripheral portion of the porous membrane 1.
[0123] Figure 4 The membrane component 2B has a breathable support material 3 disposed on one side of the porous membrane 1. The membrane component 2 may have two or more breathable support materials 3. In the membrane component 2, breathable support materials 3 may be disposed on two sides of the porous membrane 1. The porous membrane 1 and the breathable support materials 3 may be joined by welding such as thermal fusion and ultrasonic welding, or by adhesives or bonding agents.
[0124] The membrane component 2 may also have optional layers and / or components other than those described above.
[0125] The thickness of membrane component 2 is, for example, 1 μm to 300 μm. The thickness of membrane component 2 can also be 50 μm to 200 μm.
[0126] The basis weight of membrane component 2 is, for example, 1.0 g / m³. 2 ~200.0g / m 2 The basis weight of membrane component 2 can be 10.0 g / m³. 2 ~100.0g / m 2 .
[0127] The membrane component 2 may have the same properties as the porous membrane 1, such as air permeability in the thickness direction and / or water pressure resistance.
[0128] Liquid-repellent treatment and / or coloring treatment can also be applied to membrane component 2.
[0129] Membrane component 2 can be used, for example, as a filter component. However, the uses of membrane component 2 are not limited to the examples described above.
[0130] When viewed from a direction perpendicular to the main surface of membrane member 2, the shape of membrane member 2 can be, for example, a polygon including squares and rectangles, a circle, an ellipse, or a strip. The corners of the polygon can be rounded. However, the shape of membrane member 2 is not limited to the above examples. The strip-shaped membrane member 2 can also be wound to form a wound body. In addition, if necessary, it can be wound in a state of being stacked with a release liner.
[0131] Figure 5 The middle shows Figure 3 Example 2 of the deformation of the membrane component (wound body). Figure 5 The coil 10 shown includes Figure 3 The membrane component 2A and the release liner 11 are bonded together by an adhesive layer 12. In the winding body 10, the release surface 13 formed when the release liner 11 is peeled off from the membrane component 2A is located between the membrane component 2A and the adhesive layer 12. That is, in the winding body 10, the adhesive layer 12 is peeled off from the membrane component 2A when the release liner 11 is peeled off, thereby obtaining a membrane component 2A without an adhesive layer 12 formed on its surface.
[0132] The membrane member 2A, supplied by the winding body 10 and without an adhesive layer 12 formed on its surface, can be joined to the opening of the housing by any joining method. That is, the membrane member 2A has a high degree of freedom in the joining method with the opening of the housing. Joining methods include, for example, joining by a newly configured adhesive layer on the surface of the membrane member 2A, joining by thermal fusion, and joining by ultrasonic fusion.
[0133] The membrane component 2A supplied by the winding body 10 can be processed into any shape as needed. That is, the membrane component 2A has a high degree of freedom in shape. Here, "shape" includes "size". The above points mean that, according to the winding body 10, the membrane component 2A, which functions as a waterproof membrane, can be supplied in a state with a high degree of freedom in the method of joining with the opening of the shell and / or in shape.
[0134] Furthermore, according to the winding body 10, the misalignment between the film member 2A and the release liner 11 during winding is suppressed by the adhesive layer 12. In the winding body 10, the occurrence of faults (abnormal shape of the winding body) caused by winding tightness, etc., can be suppressed.
[0135] [Breathable components]
[0136] Figure 6 An example of the breathable component of the present invention is shown in the figure. Figure 6 The breathable member 4 (4A) has the porous membrane 1 or membrane member 2 described above as a member that has air permeability in the thickness direction and prevents foreign objects from passing through in that direction. The breathable member 4 is, for example, disposed on the surface of an object having an opening, ensuring air permeability through the opening while preventing foreign objects from passing through it. In this case, the breathable member 4 is typically disposed such that the porous membrane 1 or membrane member 2 covers the opening of the object. Figure 6 The breathable member 4A has a porous membrane 1. Hereinafter, the case in which the breathable member 4 has a porous membrane 1 as a member that has breathability in the thickness direction and prevents foreign objects from passing through in that direction will be described as an example.
[0137] The breathable member 4 (4A) has an adhesive layer 5 disposed on one side of the porous membrane 1. The porous membrane 1 and the adhesive layer 5 are directly bonded. The breathable member 4A can be disposed on the aforementioned surface of the object via the adhesive layer 5.
[0138] Examples of adhesives constituting adhesive layer 5 include acrylic adhesives, silicone adhesives, urethane adhesives, epoxy adhesives, and rubber adhesives. When considering the use of the breathable component 4 at high temperatures, acrylic or silicone adhesives with excellent heat resistance, especially silicone adhesives, are preferred. Adhesive layer 5 can be a substrate-free double-sided adhesive tape. The adhesive can also be a curable adhesive such as phenolic resin, epoxy resin, urea-formaldehyde resin, polyurethane resin, melamine resin, and polyester resin.
[0139] When viewed from a direction perpendicular to the main surface of the porous membrane 1, the outer periphery of the porous membrane 1 coincides with the outer periphery of the adhesive layer 5. Furthermore, when viewed from a direction perpendicular to the main surface of the porous membrane 1, the shape of the adhesive layer 5 corresponds to the shape of the peripheral portion of the porous membrane 1. The area in the porous membrane 1 that is not bonded to the adhesive layer 5 can be considered as the air-permeable area of the air-permeable member 4A. However, the shape of the adhesive layer 5 is not limited to the example described above.
[0140] The area of the breathable zone is, for example, 40mm. 2 The following describes a breathable component 4 whose breathable area falls within this range, suitable for placement on objects with small-diameter openings. The lower limit of the breathable area is, for example, 0.008 mm². 2 That's all. However, the area of the ventilated region can also be larger depending on the type of object to which the ventilated component 4 is to be installed.
[0141] Figure 7 The middle shows Figure 6 Example 1: Deformation of the breathable component. Figure 7 In addition to having an adhesive layer 5 (5B) disposed on the other side of the porous membrane 1, the breathable component 4 (4B) also has a connection with... Figure 6 The porous membrane 1 has the same structure as the breathable component 4A. The porous membrane 1 is sandwiched between a pair of adhesive layers 5 (5A, 5B).
[0142] like Figure 7 As shown, the adhesive layer 5 may include a first adhesive layer 5A bonded to one side (first main surface 1a) of the porous membrane 1 and a second adhesive layer 5B bonded to the other side (second main surface 1b) of the porous membrane 1.
[0143] Figure 8 The middle shows Figure 6 Example 2: Deformation of the breathable component. Figure 8 The breathable member 4 (4C) not only has a substrate layer 6 disposed on one side of the porous membrane 1, and the porous membrane 1 and the adhesive layer 5 are bonded through the substrate layer 6, but also has the following characteristics: Figure 6 It has the same structure as the breathable component 4A. The base material layer 6 can improve the strength and operability of the breathable component 4 and can suppress the breakage of the porous membrane 1 during operation or when placed on an object.
[0144] Examples of materials constituting the substrate layer 6 include polyolefins such as PE and PP, polyesters such as PET, silicone resins, polycarbonate, polyimide, polyamide-imide, polyphenylene sulfide, polyether ether ketone (PEEK), polyvinyl chloride, fluorinated resins, and metals such as aluminum and stainless steel. Examples of fluorinated resins include PTFE, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-ethylene copolymer (ETFE). However, the materials constituting the substrate layer 6 are not limited to the examples mentioned above.
[0145] When viewed from a direction perpendicular to the main surface of the porous membrane 1, the outer periphery of the porous membrane 1 coincides with the outer periphery of the substrate layer 6. Furthermore, when viewed from a direction perpendicular to the main surface of the porous membrane 1, the shape of the substrate layer 6 corresponds to the shape of the peripheral portion of the porous membrane 1. The area in the porous membrane 1 that is not bonded to the substrate layer 6 can be considered as the air-permeable area of the air-permeable member 4C. However, the shape of the substrate layer 6 is not limited to the example described above.
[0146] The porous membrane 1 and the substrate layer 6 can be bonded by adhesives or glues, or by welding such as thermal fusion and ultrasonic welding. The porous membrane 1 and the substrate layer 6 can also be bonded by an adhesive layer. This adhesive layer can have the same structure as adhesive layer 5. The substrate layer 6 can be a single-sided or double-sided adhesive tape.
[0147] Figure 9 The middle shows Figure 6 Example 3: Deformation of the breathable component. Figure 9 In addition to having a substrate layer 6 (6B) disposed on the other side of the porous membrane 1, the breathable component 4 (4D) also has a similar structure to... Figure 8 The porous membrane 1 has the same structure as the breathable component 4C. The porous membrane 1 is sandwiched between a pair of substrate layers 6 (6A, 6B). This clamping structure further improves the strength and operability of the breathable component 4.
[0148] like Figure 9 As shown, the substrate layer 6 may include a first substrate layer 6A bonded to one side (first main surface 1a) of the porous membrane 1, and a second substrate layer 6B bonded to the other side (second main surface 1b) of the porous membrane 1.
[0149] Figure 10 The middle shows Figure 6 Example 4: Deformation of the breathable component. Figure 10 The breathable component 4 (4E) not only has a release liner 7, and bonds the porous membrane 1 to the release liner 7 via an adhesive layer 5 (5B), but also has the characteristics of... Figure 7 The breathable component 4B has the same structure.
[0150] like Figure 10 As shown, the breathable member 4 (4E) may also have a release liner 7, with a second adhesive layer 5B disposed between the release liner 7 and the porous membrane 1, and the second adhesive layer 5B is bonded to the release liner 7.
[0151] When viewed from a direction perpendicular to the main surface of the porous membrane 1, the release liner 7 has a tab that protrudes further outward than the outer periphery of the porous membrane 1. By grasping the tab, the air-permeable member 4E can be manipulated or placed onto the surface of an object. The release liner 7 is typically removed when using the air-permeable member 4E. The release liner 7 can be made of, for example, the same material constituting the substrate layer 6. It should be noted that the release liner 7 is typically removed by grasping the tab and lifting it. At this time, a strong force is applied to the porous membrane 1 in the lifting direction. However, according to the air-permeable member 4E, the agglomeration and destruction of the porous membrane 1 is suppressed when the release liner 7 is peeled off.
[0152] Figure 11 The middle shows Figure 6 Example 5: Deformation of the breathable component. Figure 11 The breathable component 4 (4F) not only has a release liner 7, and the substrate layer 6 (6B) is bonded to the release liner 7 by an adhesive layer 5 (5B), but also has the following characteristics: Figure 9 The breathable component 4F has the same structure as the venting member 4D. According to the breathable component 4F, the porous membrane 1 is prevented from condensing and breaking down when the release liner 7 is peeled off.
[0153] Figure 12 Another example of the breathable component of the present invention is shown in the figure. Figure 12 A breathable member 4 (4G) is disposed on the surface 8s of an object 8 having a surface 8s with an opening 8p. The breathable member 4G has: a porous membrane 1 having a shape covering the opening 8p; and an adhesive layer 5 bonded to a first main surface 1a of the porous membrane 1. The breathable member 4G is fixed to the surface 8s of the object 8 using the adhesive layer 5. As described above, the porous membrane 1 contains a thermoplastic resin that does not contain fluorine-containing resin as its main component. The air permeability of the porous membrane 1, expressed in Grylls number, is 200 seconds / 100 mL or less. The object 8 bonded to the breathable member 4 (4G) can be, for example, a plate-shaped member or a shell.
[0154] The air permeability of the porous membrane 1 in the breathable component 4 (4G) can be measured either after the porous membrane 1 is separated from the bonding object 8, or when it is integrated with the object 8. The latter measurement can be performed using the aforementioned measurement method employing a SUS-made circular plate. Here, the inner diameter area of the adhesive layer 5 is defined as S[cm]. 2 When ], the area of the effective test section of the porous membrane 1 in the above formula t is [cm]. 2 ]”, using S[cm 2 ].
[0155] For the breathable component 4G, during the operation evaluation test, the porous membrane 1 did not undergo agglomeration failure until at least 0.03 N / 2.0 mm.
[0156] <Manipulation Evaluation Test>
[0157] Figure 13 This is a schematic cross-sectional view illustrating the maneuverability evaluation test of the breathable component 4G. First, a double-sided adhesive tape 55 (manufactured by Nitto Denko Corporation, No. 5605) is bonded to the second main surface 1b of the porous membrane 1, and a release liner 71 (38 μm thick) is bonded to the double-sided adhesive tape 55. The release liner 71 can be any tape that does not undergo agglomeration or breakage in the porous membrane 1 up to at least 0.03 N / 2.0 mm. For example, a polyester-based adhesive tape (No. 31B) manufactured by Nitto Denko Corporation, exhibiting a peel force of 0.6 N / 50 mm, can be used as the release liner 71. Next, a roller is moved back and forth across the release liner 71 once while a load of 2 kg is applied. Then, the breathable component 4G is cured at 60°C for 5 minutes. After curing, the breathable component 4G is left at room temperature for 15 minutes, and then the release liner 71 is grasped with tweezers and lifted to peel off.
[0158] Regarding the breathable component 4G, during the aforementioned handling evaluation test, the porous membrane 1 does not undergo agglomeration failure at least up to 0.03 N / 2.0 mm. With this configuration, agglomeration failure of the porous membrane 1 in the breathable component 4G is suppressed when installed on the housing of equipment, etc., thus exhibiting appropriate handling performance.
[0159] Figure 14 The middle shows Figure 12 A variation of the 4G breathable component. Figure 14 In addition to having an adhesive layer 5 (5B) disposed on the other side of the porous membrane 1, the breathable component 4 (4H) also has a connection with... Figure 12 The breathable component 4G has the same structure. The porous membrane 1 is sandwiched between a pair of adhesive layers 5 (5A, 5B).
[0160] In the aforementioned handling evaluation test of the breathable component 4H, it is sufficient to simply bond the double-sided adhesive tape 55 to the adhesive layer 5B on the second main surface 1b side of the porous membrane 1, and bond the release liner 71 to the double-sided adhesive tape 55.
[0161] [Component supply sheet]
[0162] The breathable component 4 can be supplied, for example, by means of a component supply sheet. Figure 15 The image shows an example of a component supply sheet used as a method for supplying the ventilating component 4. Figure 15The component supply sheet 20 (20A) includes: a breathable member 4 (4A) disposed on the surface of an object having an opening, and a substrate sheet 9 on which the breathable member 4 (4A) is disposed. The component supply sheet 20A has the breathable member 4A as the breathable member 4. The breathable member 4A includes: a porous membrane 1 having a shape that covers the opening when disposed on the surface of the object, and an adhesive layer 5 bonded to the porous membrane 1.
[0163] The breathable component 4 (4A) is disposed on the substrate sheet 9 via the adhesive layer 5. According to the component supply sheet 20 (20A), for example, the breathable component 4 can be efficiently supplied to the process of disposing of the breathable component 4 on the surface of the object.
[0164] The breathable member 4 can be disposed on the substrate sheet 9 via an adhesive layer on the disposed surface of the breathable member 4 disposed in the substrate sheet 9. The adhesive layer on the disposed surface is preferably weakly adhesive.
[0165] Although the illustration is omitted, multiple breathable components 4 can also be configured on the surface of the substrate sheet 9.
[0166] Examples of materials constituting the substrate sheet 9 include paper, metal, resin, and composites thereof. Metals include, for example, stainless steel and aluminum. Resins include, for example, polyesters such as PET, and polyolefins such as PE and PP. However, the materials constituting the substrate sheet 9 are not limited to the examples mentioned above. The substrate sheet 9 can be in the form of a single sheet or a strip. When the substrate sheet 9 is in the form of a strip, the component supply sheet 20 can be wound to form a wound body.
[0167] Examples of objects to which the venting member 4 is configured include the housing of electronic devices and the housing of electrical components for vehicles. The venting member 4 can be configured on the outer and / or inner surface of the housing. In this case, the opening can be a vent and / or a sound-transmitting opening provided in the housing. Examples of electronic devices include wearable devices such as smartwatches and wristbands; various cameras including action cameras and security monitoring cameras; information and communication devices such as mobile phones, smartphones, and tablets; virtual reality (VR) devices; augmented reality (AR) devices; and sensor devices. Examples of electrical components for vehicles include lights and ECUs. However, the objects are not limited to the above examples.
[0168] Foreign objects such as dust particles and water droplets are prevented from passing through by the configuration of the breathable component 4.
[0169] Figure 16 The middle shows Figure 15 Example 1: A variation of the component supply sheet. Figure 16 The component supply piece 20 (20B) has, in addition to having Figure 10 In addition to being a breathable component 4, the breathable component 4E has the same characteristics as... Figure 15The component supply sheet 20B has the same structure as the component supply sheet 20A. Specifically, in the component supply sheet 20B, the breathable component 4E has a porous membrane 1, a first adhesive layer 5A bonded to a first main surface 1a of the porous membrane 1, a second adhesive layer 5B bonded to a second main surface 1b of the porous membrane 1, and a release liner 7 bonded to the second adhesive layer 5B. The second adhesive layer 5B is disposed between the release liner 7 and the porous membrane 1, and the porous membrane 1 is fixed to the surface of the substrate sheet 9 using the first adhesive layer 5A. As described above, the porous membrane 1 contains a thermoplastic resin that does not contain fluorine-containing resin as its main component. The air permeability of the porous membrane 1, expressed in Gurley numbers, is 200 seconds / 100 mL or less.
[0170] It should be noted that even if the size of the porous membrane 1 in the component supply sheet 20B does not meet the recommended size (50mm×50mm) of the test sheet for the Wang Yan test machine method, the air permeability resistance (Gerley air permeability) can still be evaluated based on the Wang Yan test machine method by using a measuring fixture.
[0171] The measuring fixture has a shape and size suitable for mounting on the air permeability measuring section of a pressure testing machine, and is designed with a thickness and material that will not deform due to pressure differential applied to the test piece during air permeability resistance measurement. An example of the measuring fixture is a SUS circular plate with a thickness of 2 mm and a diameter of 47 mm. A through-hole with an opening smaller than the size of the membrane being evaluated is pre-formed at the center of the surface of the measuring fixture. The cross-section of the through-hole is typically circular, and its diameter is set such that the opening of the through-hole is completely covered by the membrane being evaluated. For example, a diameter of 1 mm or 2 mm can be used for the through-hole. Next, the first adhesive layer 5A is peeled off from the substrate sheet 9, and the porous membrane 1 being evaluated is fixed to one surface of the measuring fixture in a manner that covers the opening of the measuring fixture. The fixing is performed in such a way that, during the air permeability resistance measurement, air passes only through the effective test section of the porous membrane 1 (the portion overlapping the opening when viewed from a direction perpendicular to the main surface of the fixed porous membrane 1), and the fixed portion does not obstruct the passage of air in the effective test section of the porous membrane 1. The porous membrane 1 can be fixed using a first adhesive layer 5A. The first adhesive layer 5A is positioned between the measuring fixture and the porous membrane 1, with the periphery of the vent aligned with the periphery of the opening. Next, the release liner 7 is peeled off from the porous membrane 1, exposing the porous membrane 1. Then, the measuring fixture with the porous membrane 1 fixed is positioned in the permeability measuring section of the Wangyan testing machine, with the fixing surface of the porous membrane 1 (first main surface 1a) downstream of the airflow during measurement. The test is performed using the Wangyan testing machine method, and the permeability resistance indication value t shown by the testing machine is recorded. Then, the permeability resistance can be determined using formula t. K ={t×(area of the effective test section of porous membrane 1 [cm²])} 2 ]) / 6.452[cm 2The recorded air permeability resistance indicator value t is converted into the 6.452 cm value specified in the Wang Yan-style testing machine method. 2 The effective test area value t K and the obtained conversion value t K The air permeability resistance (Gerley air permeability) of the porous membrane 1 was determined according to the Wang Yan-style testing machine method. It should be noted that the air permeability resistance measured without the use of a measuring fixture for the porous membrane 1 with the recommended test piece size (50mm×50mm) that meets the Wang Yan-style testing machine method was confirmed to be highly consistent with the air permeability resistance measured using a measuring fixture after the porous membrane 1 was made into a small piece. That is, the use of the measuring fixture has no substantial effect on the measured value of the air permeability resistance.
[0172] When the component supply sheet 20B is subjected to the following handling evaluation test, the porous membrane 1 does not undergo agglomeration failure. Therefore, agglomeration failure of the porous membrane 1 of the component supply sheet 20B when installed on the housing of the device is suppressed, and it has appropriate handling.
[0173] <Manipulation Evaluation Test>
[0174] Figure 17 This is a schematic cross-sectional view illustrating the operability evaluation test of the component supply sheet 20B. First, the first adhesive layer 5A is peeled off from the substrate sheet 9, bringing the first adhesive layer 5A into contact with a stainless steel test plate 81, thereby placing the ventilated component 4E onto the test plate 81. Next, while applying a load of 2 kg, a roller is moved back and forth once on the release liner 7, thereby fixing the ventilated component 4E onto the test plate 81. Next, the ventilated component 4E is cured at 60°C for 5 minutes. After curing, the ventilated component 4E is placed at room temperature for 15 minutes, and then the release liner 7 is grasped with tweezers and lifted to peel it off.
[0175] Figure 18 The middle shows Figure 15 Example 2: A variation of the component supply sheet. Figure 18 The component supply sheet 20 (20C) has, in addition to having Figure 11 In addition to being a breathable component 4, the breathable component 4F has the same characteristics as... Figure 15 The components supplied are of the same composition as sheet 20A.
[0176] Example
[0177] The present invention will be further described in detail below through embodiments. The present invention is not limited to the embodiments shown below.
[0178] for Figure 1 The porous membranes shown were evaluated for their air permeability, cohesion, and other properties.
[0179] [Example 1]
[0180] Poly(4-methyl-1-pentene) resin (manufactured by Mitsui Chemicals, RT18) was used as the thermoplastic resin. A plasticizer with a kinematic viscosity of 110 mmHg at 40°C was prepared. 2 / s of liquid paraffin (manufactured by MORESCO). Pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (manufactured by BASF Japan) was used as an antioxidant. A mixture was obtained by mixing 50.0% by weight of thermoplastic resin, 49.8% by weight of plasticizer, and 0.2% by weight of antioxidant. The mixture was kneaded at 260°C for 30 minutes using a LABO PLASTOMILL (manufactured by Toyo Seiki Co., Ltd.) to obtain a homogeneous compound. 1.6g of the compound particles were sandwiched between two polyimide plates (150μm thick), further sandwiched between stainless steel plates (3.0mm thick). The particles were then hot-pressed at 1.0kN for 5 minutes using a compression molding machine heated to 260°C to obtain a pressed body. The pressed body was cooled on a metal plate at 120°C to obtain a first pressed body. The first pressed body, sandwiched between polyimide sheets, was contacted with water at 18°C to cool it, thus obtaining a molded body. Next, the molded body was subjected to simultaneous biaxial stretching using a biaxial stretching machine at a stretching temperature of 150°C and a stretch ratio of 2x (longitudinal) × 2x (transverse). The strain rate during stretching was 1% / s (0.655 mm / s) in both the longitudinal and transverse directions. This yielded a sheet. Stretching was performed 5 minutes after the molded body was placed in an oven set to the stretching temperature. Then, similar to the first hot pressing, the sheet was sandwiched between a polyimide sheet and a stainless steel sheet, and then subjected to a second hot pressing using a compression molding machine heated to 180°C at 2 kPa for 5 minutes, thus obtaining a second pressed body. Finally, extraction was performed by immersing the second pressed body in methyl ethyl ketone (MEK) at room temperature for 2 minutes using MEK as the extraction solvent. This removed the plasticizer from the second pressed body. To suppress the shrinkage of the second pressing body, the extraction operation was performed while the membrane was fixed in a stainless steel frame. Through the above operation, the porous membrane of Example 1 was obtained.
[0181] [Example 2]
[0182] The molded body was subjected to simultaneous biaxial stretching at a stretching temperature of 100°C and a stretching ratio of 2 times (longitudinal) × 2 times (transverse) to obtain a sheet. In addition, a porous membrane of Example 2 was obtained using the same method as in Example 1.
[0183] [Example 3]
[0184] The sheet was subjected to a second hot pressing at 2 kPa for 5 minutes using a compression molding machine heated to 80°C, thereby obtaining the second compressed body. In addition, the porous membrane of Example 3 was obtained using the same method as in Example 2.
[0185] [Example 4]
[0186] The sheet was subjected to a second hot pressing at 10 kPa for 5 minutes using a compression molding machine heated to 80°C, thereby obtaining the second compressed body. Otherwise, the porous membrane of Example 4 was obtained using the same method as in Example 2.
[0187] [Example 5]
[0188] The sheet was subjected to a second hot pressing at 10 kPa for 5 minutes using a compression molding machine heated to 180°C, thereby obtaining the second compressed body. Otherwise, the porous membrane of Example 5 was obtained using the same method as in Example 2.
[0189] Figure 19A A figure (2500x magnification) showing the results of SEM observation of the porous membrane surface of Example 5. Figure 19B for Figure 19A A magnified view of a portion (10,000x). Figure 19C A graph (1500x magnification) showing the results of SEM observation of the cross-section of the porous membrane of Example 5.
[0190] [Example 6]
[0191] The shaped body was subjected to simultaneous biaxial stretching at a stretching temperature of 100°C and a stretching ratio of 2.5 times (longitudinal) × 2.5 times (transverse) to obtain a sheet. In addition, the porous membrane of Example 6 was obtained using the same method as in Example 5.
[0192] [Example 7]
[0193] The molded body was subjected to simultaneous biaxial stretching at a stretching temperature of 100°C and a stretching ratio of 2 times (longitudinal) × 2 times (transverse) to obtain a sheet. The strain rate during stretching was 5% / s (3.25 mm / s) in both the longitudinal and transverse directions. In addition, the porous membrane of Example 7 was obtained using the same method as in Example 5.
[0194] [Comparative Example 1]
[0195] The sheet was not subjected to a second hot pressing, and the plasticizer was removed from the sheet. Otherwise, the porous membrane of Comparative Example 1 was obtained by the same method as in Example 1.
[0196] [Comparative Example 2]
[0197] The sheet was not subjected to a second hot pressing, and the plasticizer was removed from the sheet. Otherwise, the porous membrane of Comparative Example 2 was obtained by the same method as in Example 2.
[0198] Figure 20A A figure (2500x magnification) showing the results of SEM observation of the porous membrane surface of Comparative Example 2. Figure 20B for Figure 20A A magnified view of a portion (10,000x). Figure 20C A figure (1500x magnification) showing the results of SEM observation of the cross-section of the porous membrane in Comparative Example 2.
[0199] [Comparative Example 3]
[0200] The sheet was not subjected to a second hot pressing, and the plasticizer was removed from the sheet. Otherwise, the porous membrane of Comparative Example 3 was obtained by the same method as in Example 6.
[0201] [Comparative Example 4]
[0202] The sheet was not subjected to a second hot pressing, and the plasticizer was removed from the sheet. Otherwise, the porous membrane of Comparative Example 4 was obtained by the same method as in Example 7.
[0203] [Comparative Example 5]
[0204] The strain rate during tension was 20% / second (13.1 mm / second) in both the longitudinal and transverse directions. Otherwise, the porous membrane of Comparative Example 5 was obtained using the same method as Comparative Example 4.
[0205] [Comparative Example 6]
[0206] Poly(4-methyl-1-pentene) resin (manufactured by Mitsui Chemicals, MX 002) was used as the thermoplastic resin. A plasticizer with a kinematic viscosity of 110 mmHg at 40°C was used. 2 / s of liquid paraffin (manufactured by MORESCO). Pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (manufactured by BASF Japan) was used as an antioxidant. A mixture was obtained by mixing 35.0 wt% thermoplastic resin, 64.5 wt% plasticizer, and 0.5 wt% antioxidant. The mixture was kneaded using LABO PLASTOMILL at 260°C for 30 minutes to obtain a homogeneous compound. 1.6 g of the compound particles were sandwiched between two polyimide plates (150 μm thick), further sandwiched between stainless steel plates (3.0 mm thick), and then hot-pressed using a compression molding machine heated to 260°C at 1.0 kN for 5 minutes to obtain a first compressed body. The first compressed body, sandwiched between the polyimide plates, was contacted with water at 18°C to cool it, thereby obtaining a molded body. Prior to biaxial stretching, the molded body was annealed at 150°C for 30 minutes. Then, the annealed molded body was extracted by immersing it in MEK at room temperature for 5 minutes. Next, the molded body, after plasticizer removal, was simultaneously biaxially stretched using a biaxial stretching machine at a stretching temperature of 150°C and a stretching ratio of 3 times (longitudinal) × 3 times (transverse). The strain rate during stretching was 1% / s (0.655 mm / s) in both the longitudinal and transverse directions. This yielded a sheet. No second hot pressing was performed on the sheet. Through the above operations, a porous membrane of Comparative Example 6 was obtained.
[0207] [Comparative Example 7]
[0208] The porous membrane of Comparative Example 6 was annealed at 165°C for 5 minutes. Otherwise, the porous membrane of Comparative Example 7 was obtained by the same method as Comparative Example 6.
[0209] [Comparative Example 8]
[0210] Poly(4-methyl-1-pentene) resin (manufactured by Mitsui Chemicals, DX 845) was used as the thermoplastic resin. A plasticizer with a kinematic viscosity of 110 mmHg at 40°C was used. 2 / s of liquid paraffin (manufactured by MORESCO). Pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (manufactured by BASF Japan) was used as an antioxidant. A mixture of 55% by weight of thermoplastic resin, 44.5% by weight of plasticizer, and 0.5% by weight of antioxidant was obtained. The mixture was kneaded using LABO PLASTOMILL at 260°C for 30 minutes to obtain a homogeneous compound. 1.6g of the compound particles were sandwiched between two polyimide sheets (150μm thick), further sandwiched between two stainless steel sheets (3.0mm thick). The particles were then hot-pressed using a compression molding machine heated to 260°C at 1.0kN for 5 minutes to obtain a first pressed body. The first pressed body, sandwiched between the polyimide sheets, was contacted with water at 18°C to cool it, thus obtaining a molded body. Next, the molded body was immersed in MEK at room temperature for 5 minutes to remove the plasticizer. Then, the molded body after plasticizer removal was subjected to simultaneous biaxial stretching at a stretching temperature of 180°C and a stretching ratio of 3 times (longitudinal) × 3 times (transverse). The strain rate during stretching was 1% / s (0.655 mm / s) in both the longitudinal and transverse directions. This yielded a sheet. The sheet was not subjected to a second hot pressing, but instead underwent annealing at 170°C for 5 minutes. Through the above operations, the porous membrane of Comparative Example 8 was obtained.
[0211] The manufacturing conditions of the porous membranes of Examples 1 to 7 and Comparative Examples 1 to 8 are shown in Table 1.
[0212] Table 1
[0213] ※1: Plasticizer extraction and removal performed before stretching.
[0214] Using the methods described above for porous membranes, the thickness, air permeability, water pressure resistance, cohesion, and controllability of the porous membranes of Examples 1 to 7 and Comparative Examples 1 to 8 were evaluated. The evaluation results are shown in Table 2. Controllability was evaluated as follows.
[0215] A: When the peeling liner is grasped with tweezers and lifted to peel it off, the porous membrane does not undergo coagulation or destruction.
[0216] B: When the peeling liner is grasped with tweezers and lifted to peel it off, the porous membrane undergoes coagulation and destruction.
[0217] Table 2
[0218] As shown in Table 2, the porous membranes of Examples 1 to 7 exhibit air permeability (Gerly number) of less than 200 seconds / 100 mL and cohesion of more than 1.0 N / 20 mm, and demonstrate excellent controllability (A). Therefore, the porous membranes of Examples 1 to 7 achieve a balance between controllability and air permeability.
[0219] Depend on Figures 19A-19B and Figures 20A-20B A comparison reveals that the porous membranes of both Example 5 and Comparative Example 2 have a tortoise-shell-like structure formed by multiple nodes and multiple fibrils on their surfaces. However, due to... Figure 19C and Figure 20C The comparison shows that, in the thickness direction, the porous membrane of Example 5 exhibits smaller deviations in the size of the gaps between the island-like regions formed by multiple nodes, and the gaps are dispersed. In contrast, the porous membrane of Comparative Example 2 shows deviations in the size of the gaps, with large and small gaps mixed together. Based on this result, it can be inferred that in the porous membrane of Example 5, the smaller deviations in the size of the gaps in the thickness direction and the dispersed nature of the gaps enhance the cohesiveness of the porous membrane.
[0220] Based on the above results, it can be understood that the porous membranes of Examples 1 to 7 are suitable for balancing operability and air permeability.
[0221] Next, regarding Figure 12 The breathable components shown were evaluated for breathability and maneuverability.
[0222] [Example 8]
[0223] The porous membrane of Example 1 was cut into a circle with a diameter of 5.8 mm and used as a breathable component. A stainless steel (SUS) circular plate with a thickness of 2 mm and a diameter of 47 mm, having an opening with a circular cross-section of 1 mm in the center, was used as the object. Double-sided adhesive tape (manufactured by Nitto Denko Corporation, No. 5605) with a vent (1.6 mm in diameter) punched out in the center to match the shape of the opening was used as the adhesive layer. The breathable component of Example 8 was obtained through the above operations.
[0224] Using the method described above for the breathable component 4G, the air permeability and maneuverability of the breathable component of Example 8 were evaluated. The evaluation results are shown in Table 3. Maneuverability was evaluated as follows.
[0225] C: When the peeling liner is grasped with tweezers and lifted to peel it off, the porous membrane does not undergo agglomeration or damage until at least 0.03 N / 2.0 mm.
[0226] D: When the peeling liner is grasped with tweezers and lifted to peel it off, the porous membrane undergoes agglomeration and destruction before reaching 0.03 N / 2.0 mm.
[0227] Table 3
[0228] As shown in Table 3, for the breathable component of Example 8, the air permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL. Furthermore, the porous membrane has a peel strength of 0.03 N / 2.0 mm or higher. Therefore, the breathable component of Example 8 balances the operability and breathability of the porous membrane.
[0229] It should be noted that Example 8 is a breathable component using the porous membrane of Example 1. Therefore, according to the results of the cohesion test of Example 1 in Table 2 and the controllability evaluation test of Example 8 in Table 3, the cohesion of the porous membrane is 1.2 N / 20 mm, which is synonymous with the peeling force of the porous membrane in the breathable component using the porous membrane being 0.03 N / 2.0 mm.
[0230] Next, regarding Figure 16 The components supplied with the shown method were evaluated for air permeability and controllability.
[0231] [Example 9]
[0232] The porous membrane of Example 1 was cut into circles with a diameter of 5.8 mm and used as a breathable component. As the substrate sheet, a double-sided adhesive tape (manufactured by Nippa Corporation, release grade J0L) was used. As the first and second adhesive layers, a double-sided adhesive tape (manufactured by Nitto Denko Corporation, No. 5605) with a vent (1.6 mm in diameter) punched out at the center to match the shape of the opening was used. As the release liner, a release liner exhibiting a peel force of 0.6 N / 50 mm in polyester substrate adhesive tape (No. 31B) manufactured by Nitto Denko Corporation was used. The second adhesive layer was disposed between the release liner and the porous membrane. The porous membrane was fixed to the surface of the substrate sheet using the first adhesive layer. Through the above operations, the component supply sheet of Example 9 was obtained.
[0233] Using the method described above for the component supply sheet 20B, the air permeability and controllability of the component supply sheet of Example 9 were evaluated. The evaluation results are shown in Table 4. The controllability was evaluated as follows.
[0234] E: When the peeling liner is grasped with tweezers and lifted to peel it off, the porous membrane does not undergo coagulation or destruction.
[0235] F: When the peeling liner is lifted and peeled off by tweezers, the porous membrane undergoes coagulation and destruction.
[0236] Table 4
[0237] As shown in Table 4, the porous membrane of the component supply sheet of Example 9 exhibits a permeability of less than 200 seconds / 100 mL, expressed as a Grylls number. Furthermore, the porous membrane demonstrates excellent controllability (E). Therefore, the component supply sheet of Example 9 combines the controllability and permeability of a porous membrane.
[0238] Industrial practicality
[0239] The technology of this invention can be applied, for example, to waterproof and breathable membranes, waterproof and sound-permeable membranes, and separators for energy storage devices.
Claims
1. A porous membrane, wherein, The porous membrane contains a fluorine-free thermoplastic resin as its main component. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and The cohesive strength of the porous membrane is above 1.0 N / 20 mm.
2. The porous membrane according to claim 1, wherein, The thermoplastic resin is a polyolefin resin.
3. The porous membrane according to claim 1, wherein, The thickness of the porous membrane is greater than 40 μm and less than 100 μm.
4. The porous membrane according to claim 1, wherein, The porous membrane has a water pressure resistance of over 200 kPa.
5. The porous membrane according to claim 1, wherein, The porous membrane is a stretched membrane.
6. A breathable component, wherein, The breathable component has: The porous membrane according to any one of claims 1 to 5; and An adhesive layer that bonds to the porous membrane.
7. The breathable component according to claim 6, wherein, The adhesive layer comprises: The first adhesive layer bonded to the first main surface of the porous membrane, and A second adhesive layer that bonds to the second main surface of the porous membrane.
8. The breathable component according to claim 7, wherein, The breathable member also has a release liner, and a second adhesive layer is disposed between the release liner and the porous membrane, the second adhesive layer being bonded to the release liner.
9. A breathable member disposed on said surface of an object having an opening, wherein, The breathable component has: A porous membrane having a shape that covers the opening; and A first adhesive layer is bonded to the first main surface of the porous membrane. The breathable component is fixed to the surface of the object using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operability evaluation test was performed, the porous membrane did not undergo aggregation or damage until at least 0.03 N / 2.0 mm. <Manipulation Evaluation Test> Double-sided adhesive tape is bonded to the second main side of the porous membrane, and a release liner is bonded to the double-sided adhesive tape; then, while applying a load of 2 kg, the roller is moved back and forth once on the release liner; then, the breathable component is cured for 5 minutes at 60°C; the cured breathable component is placed at room temperature for 15 minutes, and then the release liner is grasped with tweezers and lifted to peel it off.
10. The breathable member according to claim 9, wherein, The breathable component has a second adhesive layer that bonds to the second main surface of the porous membrane.
11. A component supply sheet, the component supply sheet comprising: A breathable member disposed on the surface of an object having an opening; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; and An adhesive layer is bonded to the porous membrane. The porous membrane is the porous membrane according to any one of claims 1 to 5.
12. The component supply sheet according to claim 11, wherein, A plurality of the breathable members are disposed on the surface of the substrate sheet.
13. A component supply sheet, the component supply sheet comprising: A breathable member disposed on the surface of an object having an opening; and a substrate sheet having the breathable member disposed on its surface, wherein... The breathable component has: A porous membrane having a shape that covers the opening when disposed on the surface; A first adhesive layer is bonded to a first main surface of the porous membrane; A second adhesive layer is bonded to the second main surface of the porous membrane; and The release liner is then bonded to the second adhesive layer. The second adhesive layer is disposed between the release liner and the porous membrane. The breathable component is fixed to the surface of the substrate sheet using the first adhesive layer. The porous membrane contains a thermoplastic resin as its main component, and the thermoplastic resin does not contain fluorinated resin. The permeability of the porous membrane, expressed as a Grylls number, is less than 200 seconds / 100 mL, and, When the following operational evaluation tests were performed, the porous membrane did not undergo aggregation or damage. <Manipulation Evaluation Test> Peel the first adhesive layer from the substrate sheet, bringing the first adhesive layer into contact with a stainless steel test plate, thereby placing the breathable component on the test plate; then, while applying a 2 kg load, roll the roller back and forth once on the release liner, thereby fixing the breathable component on the test plate; next, perform a curing treatment on the breathable component at 60°C for 5 minutes; place the cured breathable component at room temperature for 15 minutes, and then use tweezers to grasp the release liner and lift it to peel it off.
14. The component supply sheet according to claim 13, wherein, A plurality of the breathable members are disposed on the surface of the substrate sheet.
15. A method for manufacturing a porous membrane, wherein, The method for manufacturing the porous membrane includes: The process of mixing a composition containing a fluorine-free thermoplastic resin and a plasticizer to obtain a compound; The process of performing compression or extrusion processing; The process of implementing cooling treatment; The process of performing stretching treatment; and The process of extracting and treating plasticizers is implemented. Following the stretching process, a pressing process is also included.
Citation Information
Patent Citations
Olefin resin microporous biaxially oriented film, method for producing the same, heat-resistant olefin resin microporous biaxially oriented film, and method for producing the same
JP2017095576A
